2022
DOI: 10.1007/978-3-030-99194-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Unique App Signature of the Depressed and Non-depressed Through Their Fingerprints on Apps

Abstract: Growing research on re-identification through app usage behavior reveals the privacy threat in having smartphone usage data to third parties. However, re-identifiability of a vulnerable group like the depressed is unexplored. We fill this knowledge gap through an in the wild study on 100 students' PHQ-9 scale's data and 7 days' logged app usage data. We quantify the uniqueness and re-identifiability through exploration of minimum hamming distance in terms of the set of used apps. Our findings show that using a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 53 publications
(117 reference statements)
3
29
0
Order By: Relevance
“…SHAP analysis [4] on our best ML model NB based on the IG selected 17 features showed that the lonely students were more likely to have a higher variation in duration per app on weekdays over the 4 time periods. This finding aligns with the studies conducted through conventional statistical methods showing depressed students' variation of diurnal app usage patterns [17,38]. The variation can reflect students' mood swings while going through a negative experience [24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…SHAP analysis [4] on our best ML model NB based on the IG selected 17 features showed that the lonely students were more likely to have a higher variation in duration per app on weekdays over the 4 time periods. This finding aligns with the studies conducted through conventional statistical methods showing depressed students' variation of diurnal app usage patterns [17,38]. The variation can reflect students' mood swings while going through a negative experience [24].…”
Section: Discussionsupporting
confidence: 90%
“…However, students used several apps which were not available there, and thus, using the package name, we explored the features of those apps in online app stores (e.g., apkmonk.com) and developers' websites. Finally, we categorized the apps by understanding the app categorization process of previous studies (e.g., [17]) and through a discussion with 2 graduate students of the engineering faculty. We found 105 students using 867 apps of 26 categories (Fig.…”
Section: Feature Extraction and App Usage Behavioral Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Smartphones have become affordable [82] and are available to the majority of adults in emerging and developing countries [16]. Smartphone usage has a significant relation with depression [27,28,44,45] and loneliness [40,41,42]. In addition, higher levels of depression are linked with higher usage and a higher number of times interacting on the phone [44].…”
Section: Introductionmentioning
confidence: 99%